2018
DOI: 10.1002/gj.3400
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of siltstones of the Early Cretaceous Laiyang Group in Taolin area, Shandong Province, Eastern China: Implications for provenance, source weathering, palaeo‐environment, and tectonic setting

Abstract: The depositional environment and tectonic setting of the newly identified Ri-Qing-Wei Basin are the focus of controversy. In order to solve these questions, the geochemical characteristics of siltstones from Laiyang Group in Taolin area are analysed in detail. The siltstones present similar contents of SiO 2 and Al 2 O 3 compared with upper continental crust (UCC) and post-Archean Australian Shale (PAAS) and are classified as wacke on chemical classification plot of clastic rocks. The trace elements are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…The A–CN–K ternary plot (Figure 8; Al 2 O 3 –(CaO* + Na 2 O)–K 2 O) is a reliable tool for monitoring weathering trends (Kasanzu et al, 2008; Moosavirad et al, 2011; Ogala, 2022; Ramirez‐Montoya et al, 2021; Wang et al, 2012; Zeng et al, 2020; Zhang et al, 2018). As a result of the metasomatism of potassum, the weathering trend tends to be in the direction of illite and muscovite at A–K and close to the A vertex (Fedo et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A–CN–K ternary plot (Figure 8; Al 2 O 3 –(CaO* + Na 2 O)–K 2 O) is a reliable tool for monitoring weathering trends (Kasanzu et al, 2008; Moosavirad et al, 2011; Ogala, 2022; Ramirez‐Montoya et al, 2021; Wang et al, 2012; Zeng et al, 2020; Zhang et al, 2018). As a result of the metasomatism of potassum, the weathering trend tends to be in the direction of illite and muscovite at A–K and close to the A vertex (Fedo et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…is a reliable tool for monitoring weathering trends (Kasanzu et al, 2008;Moosavirad et al, 2011;Ogala, 2022;Ramirez-Montoya et al, 2021;Wang et al, 2012;Zeng et al, 2020;Zhang et al, 2018).…”
Section: Trace Elementsmentioning
confidence: 99%
“…(2) Tectonic setting in the Late Devonian It has been shown that the chemical compositions of the sediments can be related to plate tectonic processes, making geochemistry a powerful tool for recognizing ancient tectonic settings [50,[76][77][78]. The value of K 2 O/Na 2 O of sedimentary rock behaves differently from its SiO 2 content in different tectonic settings.…”
Section: Tectonic Implicationmentioning
confidence: 99%
“…Among them, the cumulative thickness of dark mudstone is 520 m, and the cumulative thickness of dark argillaceous siltstone and siltstone is 450 m. Overall, the Laiyang Formation in well LK-1 is a potential high-quality source-rock development horizon with dark fine-grained deposits [10] (Figure 1d). [24]); (b) geological map of the Riqingwei basin (modified from [25]); (c) geological map of the Lingshan Island, location of well LK-1(modified from [22]); and (d) composite stratigraphic column and sampling locations of the Laiyang Formation in well LK-1(modified from [22]).…”
Section: Geological Settingmentioning
confidence: 99%
“…Methods for evaluating organic-matter abundance in source-rock samples include TOC content determination, rock pyrolysis analysis and Chloroform bitumen "A" content [24]); (b) geological map of the Riqingwei basin (modified from [25]); (c) geological map of the Lingshan Island, location of well LK-1(modified from [22]); and (d) composite stratigraphic column and sampling locations of the Laiyang Formation in well LK-1(modified from [22]).…”
Section: Geochemical Analysismentioning
confidence: 99%